The slope/y-intercept form of a linear equation is y = mx + b, where m is the slope (∆y/∆x) and b is the y-intercept, the point where the line intersects the y axis. Therefore,y = 6x - 2
9
x-intercept = (-6, 0)
If the y intercept is -6 then the equation is: y = -7x-6
To find the x and y intercepts of this function, you should first put the equation in the form y=mx+b. In this equation b represents your y intercept and by plugging 0 in for y and solving for x you can find your x intercept. So first, let's convert 2x-3y=-6 to y=mx+b. 2x-3y=-6-->subtract 2x from each side -3y= -6-2x --> now divide each side by -3 y= (-6/-3) -(2/-3)x --> y=2+2/3x or y=2/3x + 2 So now if you plug in 0 for x you can solve for your y intercept. y= 2/3(0) +2--> y=2 and to solve for your x intercept, plug in 0 for y. 0=2/3x +2 --> subtract 2 from both sides. -2= 2/3x --> divide each side by 2/3 or multiply by 3/2 -2 * 3/2=x x=-6/2 or -3 ANS: y intercept= 2 and x intercept= -3
Points: (2, 0) and (0, -6) Slope: 3 Equation: y = 3x -6
If you mean: 3y = 9x+6 then y = 3x+2 whereas 2 is the y intercept and 3 is the slope
-6
-3X + 3Y = 6 3Y = 3X + 6 Y = X + 2 slope(m) = 1 Y intercept = 2 Another way to find Y intercept is to 0 out X in first equation -3(0) + 3Y = 6 3Y = 6 Y = 2
The slope/y-intercept form of a linear equation is y = mx + b, where m is the slope (∆y/∆x) and b is the y-intercept, the point where the line intersects the y axis. Therefore,y = 6x - 2
The y intercept is -6
If: 2y-4x = -12 Then: y = 2x-6 So the y intercept is -6 and the slope is 2
2y - 4x = -12 Algebraically rearrange to 2y = 4x - 12 Divide both sides by '2' y = 2x - 6 So at the 'y' intercept, x = 0 Substituting x = 0 We have y = 2(0) - 6 Anything multiplied '0' is equal; to '0' Hence y = 0 - 6 y = -6 is the value of the y-intercept.
9
-8
x-intercept = (-6, 0)
To determine the x - intercept put y = 0 (and conversely the y - intercept is shown when x = 0) y = 4x + 6 0 = 4x + 6 4x = -6 x = -6/4 = -3/2 (or -1.5)